Mihai Viteazul (I-II) - Nicolaescu, Sergiu (Romania : Romania Film, 1970)
This Romanian historical epic features the efforts of Prince Michael the Brave to unify the Romanian-inhabited principalities of Wallachia, Moldova, and Transylvania during the late Middle Ages. It shows his battles along with the political intrigues, scurvy treacheries, and family dramas. The first part of the film is entitled "Calugareni", named after the battle where Michael managed to stall the Ottoman offensive in the Balkans. The second is called "The Unification", presenting his attempts to unify the three Principalities as well as the way this bold endeavor ultimately failed. One of the largest, most complex, and most expensive films to be made in Romania in its time. The original version consisted of two parts and was over four hours long. The version released in Europe in 1973 is about two hours long.
Keywords: Fiction films